ANALISIS KESALAHAN PENEMPATAN ADVERBIAL (状语) DALAM KALIMAT BAHASA MANDARIN (Longda Xiaokan: Journal of Mandarin Learning and Teaching, 2018)
Abstract___________________________________________________________________状语(adverbial) is an additional component in the front center of a verb, the form of an adjective.The basic function of adverbial is limiting and modifying the word center. Adverbial placement in Mandarin language is different from the adverbial placement in Indonesian sentences so that students often make mistakes in adverbial placement when creating Mandarin phrases. Furthermore, errors also occur when there are some adverbials in a sentence that makes adverbial must be placed based on the rules of order. This research tends to determine the type of adverbial placement errors and how to solve adverbial placement errors in a Mandarin sentence. This study used qualitative descriptive approach. The object of this research is the 43 eleventh grade students of SMA YSKI Semarang who choose Mandarin language lessons. Based on this research, the causes of students’ errors (respondents) are due to the influence of the use of Indonesian language and less understanding of the adverbial order, the correct adverbial sentence structure and the vocabulary. From those factors above, the researcher propose some suggestions in order to reduce the occurrence of adverbial placement errors, such as comprehending Mandarin sentence structure with simple formulas subject + adverbial + predicate + object, the placement of multi adverbial in the correct order, and also to enrich the vocabulary. Abstrak___________________________________________________________________ 状语（adverbial）adalah komponen tambahan di depan pusat kata kerja,kata sifat. Fungsi dasar adverbial adalah membatasi dan memodifikasi pusat kata. Penempatan adverbial dalam bahasa madarin berbeda dengan penempatan adverbial di dalam kalimat bahasa indonesia sehingga siswa sering melakukan kesalahan dalam penempatan adverbial saat membuat kalimat bahasa mandarin. Selain itu, kesalahan juga terjadi ketika di dalam sebuah kalimat terdapat beberapa adverbial, adverbial harus diletakkan berdasarkan aturan urutannya. Penalitian ini bertujuan untuk mengetahui jenis kesalahan penempatan adverbial  dan cara mengatasi  kesalahan penempatan adverbial dalam kalimat bahasa mandarin. Penelitian ini menggunakan pendekatan deskriptif kualitatif. Objek penelitian ini adalah siswa kelas XI SMA YSKI Semarang yang memilih pelajaran bahasa mandarin yang berjumlah 43 siswa. Berdasarkan hasil penelitian, faktor penyebab kesalahan siswa (responden) dikarenakan adanya pengaruh bahasa indonesia, tidak memahami urutan adverbial, tidak mengetahui struktur kalimat beradverbial yang benar, serta tidak memahami kosakata. Dari faktor penyebab diatas, peneliti merumuskan beberapa saran agar dapat mengurangi terjadinya kesalahan penempatan adverbial dengan mememahami struktur kalimat bahasa mandarin dengan rumus sederhana subjek + adverbial + predikat + objek. Penempatan multi adverbial dengan urutan yang tepat, serta memperbanyak pembendaharaan kosakata.